Scorpion envenoming by tityus discrepans pocock, 1897 in the northern coastal region of Venezuela - Reyes Lugo, Matías; Rodríguez Acosta, Alexis (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
One thousand and forty five scorpion-envenomed (SE) patients studied from 1990 to 1996 were analyzed. Depending on symptom intensity, these cases were distributed in categories: 1) Light Scorpion Envenoming (LSE) 72.06% expressed only a few symptoms like pain at the sting site: followed by 2) Moderate Scorpion Envenoming (MSE) with 16.55%,: and Intense Scorpion Envenoming with 9.95%, and finally a group of patients classified as 4) Severe Scorpion Envenoming (SSE), with 1.44%. The proportion of envenomed subjects was analysed by age group and sex. In a comparison of the percentages SE by age groups classified by the Student T-test (p < 0.05), showed no significant differences for the distribution of cases in the ages over 10 years old, but the number of cases for ages under 10 years was significant. Towns located at altitudes of over 1,000 meters had the highest scorpion envenoming indexes: San Antonio de Los Altos- Los Teques (26.2%), Baruta-Hatillo-Hoyo de la Puerta (19.8%), El Junquito (15.4%). These localities accounted for 61.4% of scorpion envenoming, while 38.6% were distributed in ten towns down 800 meters. The envenoming could occur at any moment of the day, although the highest incidence (69.3%) was between 6:00 AM and 6:00 PM. A detailed analysis of the scorpion envenoming time distribution indicated that the highest percentage (42.8%) was concentrated from 6:00 AM to 12:00 M. In Caracas the incidence of SE constitutes a potentially significant epidemic situation, when we take into account that in Caracas we find a highly concentrated human population together with a highly dangerous scorpion, Tityus discrepans, Pocock, 1897.